Rapunzel - Bryant, Megan E.; Huxtable, Tonja; Huxtable, John (New York : Grosset & Dunlap, 2007)
An adaptation of the traditional tale, featuring Strawberry Shortcake and her friends.
"Strawberry Shortcake."
Keywords: Fairy tales -- Adaptations -- Juvenile fiction